EFFECTIVENESS OF GUAVA LEAVES ON PROLONGING THE HEALING TIME OF PERINEAL WOUNDS IN POSTPARTUM MOTHERSIN THE WORKING AREA OF BLANG MANGAT COMMUNITY HEALTH CENTER - Siska Desta Roza; Nia Afnita Rizana; Siti Lestari; Ridha andria (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Perineal wounds are one of the causes of postpartum infections that can slow the recovery process of postpartum mothers if not treated properly. This study aims to analyze the effectiveness of guava leaf decoction on the healing time of perineal wounds in postpartum mothers in the working area of ​​Blang Mangat Community Health Center. The study used a quantitative approach with a quasi-experimental design through a two-group post-test only design. The study population was 68 postpartum mothers on the first day, while the sample was 30 respondents consisting of 15 respondents in the guava leaf group and 15 respondents in the binahong leaf group selected using accidental sampling. The research instruments included REEDA scale observation sheets, food recall, questionnaires, interview guidelines, SOPs, and checklists. Data analysis was carried out univariately and bivariately using the Mann Whitney test. The results showed that the average healing time of perineal wounds in the guava leaf group was 5.47 days and 5.63 days in the binahong leaf group, with a p-value of 0.003. It was concluded that giving boiled guava leaves was more effective than binahong leaves in accelerating the healing of perineal wounds in postpartum mothers, so it has the potential to be an alternative non-pharmacological treatment during the postpartum period.